Trans-activation of the Tetrahymena group I intron ribozyme via a non-native RNA-RNA interaction. - Ikawa, Y (1999)
The peripheral P2.1 domain of the Tetrahymena group I intron ribozyme has been shown to be non-essential for splicing. We found, however, that separately prepared P2.1 RNA efficiently accelerates the 3' splice-site-specific hydrolysis reaction of a mutant ribozyme lacking both P2.1 and its upstream region in trans. We report here the unusual properties of this trans-activation. Compensatory mutational analysis revealed that non-native long-range base-pairings between the loop region of P2.1 RNA and L5c region of the mutant ribozyme are needed for the activation in spite of the fact that P2.1 forms base-pairings with P9.1 in the Tetrahymena ribozyme. The trans -activation depends on the non-native RNA-RNA interaction together with the higher order structure of P2.1 RNA. This activation is unique among the known trans-activations that utilize native tertiary interactions or RNA chaperons.